Evaluasi Sistem Pemberian Kredit Pada PT ABC - Nur Dina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to assess the process of granting credit to PT ABC, especially how the process of applying for and disbursing credit. The research was conducted by looking at and talking with PT ABC employees. The results show that PT ABC's lending procedure is running in accordance with the current procedure. Sales handle credit applications, and prospective debtors are briefed on credit terms. The survey head enters the survey data into the system for further study. Credit disbursement after leadership approval and administrative research Collateral documents and credit cards are given to debtors who pay off their credit. The submitted documents are eligible for credit. This study improves our understanding of how PT ABC provides credit and offers suggestions for improvement.